Meaning Strengthen Your Heart And Behave Like A Man 1 Kings 2:2 - Jeremia J. Hutajulu; Helena Putri Sibarani; Jessi Manuella Hasugian; Icha Christian Silalahi (STT BNKP Sundermann, 2023)
The behavior of God's people in interpreting words often results in misinterpretation, so that this causes mistakes in interpreting certain words in the Bible. However, this is only a misunderstanding, because the Bible is never wrong, but human thinking does not reach the contents of the Bible. This study aims to provide a deeper understanding so that readers can understand the meaning of words like